The letters of George Santayana. - Santayana, George, 1863-1952 (Santayana, George, 1863-1952. Works. 1986 ;, 2002)
The third of eight books of the correspondence of George Santayana. Book Three of George Santayana's letters covers a period of intense intellectual activity in Santayana's life, and the correspondence reflects the establishment of his mature philosophy. Santayana becomes more permanently established in Italy, but continues to travel in France, Spain, and England. The year 1927 marks the beginning of his long friendship with Daniel Cory, who became his literary secretary and eventually his literary executor. Also, with the death of Santayana's half-brother Robert, George Sturgis, Robert's son, becomes an important part of Santayana's life and letters as his financial manager. Santayana continues to write to his sister Susana, as well as to numerous friends and fellow philosophers, including Bernard Berenson, Robert Seymour Bridges, Curt John Ducasse, John Erskine, Horace Meyer Kaller, Lewis Mumford, George Herbert Palmer, John Francis Stanley Russell, Herbert Wallace Schneider, Charles Augustus Strong, Paul Weiss, and Harry Austryn Wolfson. Other correspondents include Wendell T. Bush, Alys Gregory, Marianne Moore, John Middleton Murray, and Frederick J.E. Woodbridge.